Ideologi Gender dalam Konstruksi Kurikulum Program Studi di Universitas Negeri Semarang - Yanuari Dwi Puspitarini; Yuli Utanto (Teknodika, 2019)
The purpose of this study is to find out how far the gender ideology influence students in choosing courses and how the curriculum construction which is developed by Early Childhood Education and Physical, Sports and Recreation teacher program. This research is a qualitative research with phenomenological approach. This research was conducted at the teacher education of three programs (early childhood education, physical, sports and recreation program) in Universitas Negeri Semarang. The subjects of this research are the students and the lecturers of each study program. The technique of data collection in this research used an interview technique. The results of this research are gender ideology did not directly affect the students in choosing a specific study program, but it begins from the parenting system that is applied by the parents. The  structure of curriculum in each study program is arranged in appropriate with the demands in the employment industry